1992
DOI: 10.1902/jop.1992.63.6.515
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic, Chemotactic, and Synthetic Responses of Rat Periodontal Ligament Fibroblastic Cells to Polypeptide Growth Factors In Vitro

Abstract: The mitogenic, chemotactic, and synthetic responses of rat periodontal ligament (PDL) fibroblastic cells to epidermal growth factor (EGF), transforming growth factor-beta (TGF-beta), recombinant human platelet-derived growth factor (rhPDGF)-AB, rhPDGF-BB, natural (n) PDGF-AB, and insulin-like growth factor-I (IGF-I) were examined in vitro using PDL cells obtained from the coagulum of healing tooth sockets. PDGFs and IGF-I have potent and comparable mitogenic effects on PDL fibroblastic cells. The maximum mitog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
195
1
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(210 citation statements)
references
References 32 publications
8
195
1
6
Order By: Relevance
“…Shortly after tooth extraction, the socket is filled with blood coagulum formed by blood vessel breakage from the periodontal ligament and apical foramen. There are four morphologic phases in the process of alveolar repair (2,14). The first phase refers to cellular proliferation and infiltration of the coagulum by fibroblasts from the periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after tooth extraction, the socket is filled with blood coagulum formed by blood vessel breakage from the periodontal ligament and apical foramen. There are four morphologic phases in the process of alveolar repair (2,14). The first phase refers to cellular proliferation and infiltration of the coagulum by fibroblasts from the periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…All of these participate in the wound-healing process, but, until now, only the three isoforms PDGF-AA, BB and AB were evaluated in periodontal therapy. PDGF-BB is the most effective on PDL cell mitogenesis and matrix biosynthesis [75,76]. Several preclinical studies were performed using the combination of PDGF-BB and IGF-I for periodontal and peri-implant bone regeneration [77][78][79][80][81][82], culminating in the first study in humans using growth factors for periodontal regeneration [83].…”
Section: Growth Factor Applications For Oral and Periodontal Tissue Ementioning
confidence: 99%
“…Lynch et al demonstrated that short-term application of a combination of plateletderived growth factor and insulin-like growth factor can enhance the formation of the periodontal attachment apparatus 5-10 fold during the early phase of wound healing. Matsuda et al studied the effects of individual and a combination of growth factors on PDL fibroblasts [21,22].…”
Section: Growth Factorsmentioning
confidence: 99%